ANALISIS MEDIA MONITORING PUBLIK TERHADAP FENOMENA BOIKOT PRODUK MENGGUNAKAN BRAND24 - Bambang Sri Hartono; Herni Nursetiana (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The pro-Israel product boycott movement is a very popular and hotly discussed topic on social media, both in Indonesia and internationally. This study aims to identify the atmosphere, trends, and variations of opinions that develop among social media users regarding the issue of product boycotts. This research uses a media monitoring method with a quantitative approach. This research explores data with Brand24 media monitoring with research subjects in the form of social media content, mass media, and non-media. The object of this research is a discussion related to the product boycott phenomenon within a certain time span. Based on the results of the analysis conducted, it is concluded that on the topic of product boycott, the mention volume data was obtained 1337 times. Where the most media is on social media, namely X (Twitter) as many as 551. Meanwhile, in mass media such as Web, News, and Blogs have fewer parts discussing the topic of product boycotts. Based on the analysis of product boycott topics, accounts such as info_hidup.sehat, Talk Show tvOne RELOAD, Awal Hanan, AnwarOjat, pituturid_, and YRUHIYAT200 are the most active profiles responding, with Talk Show tvOne RELOAD acting as an interactive program presenting public figures related to the theme of the show. In addition, based on top profile data on non-social media, the okezonenews account has the highest influence with the largest audience and often presents the latest news. The majority of conversations were sourced from Twitter, with a dominance of negative sentiment of 298, compared to positive sentiment of only 37. Negative sentiment experienced several significant peaks, indicating an increased interest in product boycotts at several points in time, while positive sentiment tended to fluctuate with an increasing trend towards the end of the period.